2015
DOI: 10.1097/cad.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

SW480 colorectal cancer cells that naturally express Lgr5 are more sensitive to the most common chemotherapeutic agents than Lgr5-negative SW480 cells

Abstract: Leucine-rich repeat containing G protein-coupled receptor 5 (Lgr5) is a colorectal cancer (CRC) stem cell marker. The role of Lgr5-expressing stem cells in resistance to chemotherapy is controversial. The notion that Lgr5-expressing cells are more chemotherapy resistant is supported by some data; other data do not support this notion. We hypothesized that Lgr5-expressing cells would be more chemotherapy sensitive, as Lgr5 is usually a marker of dividing cells. We tested this hypothesis by exploiting two natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Importantly, cancer cell lines helped to reveal the molecular mechanisms underlying multiple diseases, including, but not exclusively, cancer. Despite the controversy surrounding their use [36,37], cancer cell lines are still a valuable "in vitro" model system, widely used in cancer research, identification of biomarkers, and drug discovery [38][39][40]. Lipid research has been no exception in the use of this model, as could not have been otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cancer cell lines helped to reveal the molecular mechanisms underlying multiple diseases, including, but not exclusively, cancer. Despite the controversy surrounding their use [36,37], cancer cell lines are still a valuable "in vitro" model system, widely used in cancer research, identification of biomarkers, and drug discovery [38][39][40]. Lipid research has been no exception in the use of this model, as could not have been otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to several factors. First, the role of LGR5 in chemotherapy resistance is controversial, although Planutis et al ( 35 ) reported that LGR5-expressing CRC cells were more sensitive to anticancer drugs. Second, single irradiation in vitro is different from multiple courses of irradiation in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…To address residual disease systematically, characteristics of cells responsible for it should be examined. Considering the multigenetic nature of colorectal cancer, preference for a single marker of those cells responsible for the residual disease, such as leucine rich repeat containing G proteincoupled receptor 5 (LGR5), does not look promising (23), and analysis of activity in regulatory pathways including WNT signaling pathway seems to be more desirable.…”
Section: Discussionmentioning
confidence: 99%